Associations of exposure to phthalate with serum uric acid and hyperuricemia risk, and the mediating role of systemic immune inflammation - Zhiping Niu; Tianyi Chen; Zhizhou Duan; Shichao Han; Yifan Shi; Wenyuan Yu; Shuang Du; Hao Tang; Wenpu Shao; Jin Sun; Han Chen; Yunfei Cai; et al. (Ecotoxicology and Environmental Safety)
Background: Previous studies found that urinary phthalates (PAEs) metabolites may be associated with increased serum uric acid concentration and hyperuricemia risk. However, no population-based study has investigated the underlying biological mechanisms. Methods: This nationwide cross-sectional study analyzed the data from the National Health and Nutrition Examination Survey (NHANES) 2003–2018. Urinary PAEs metabolites were measured and 8 PAEs metabolites (MCPP, MECPP, MEHHP, MEOHP, MBzP, MiBP, MBP, and MEP) were incorporated into the analysis. Serum uric acid was determined and hyperuricemia cases were identified. Multi-variable generalized linear model, exposure-response (E-R) function and weighted quantile sum (WQS) regression were utilized to investigate the relationships of PAEs metabolites with serum uric acid concentration and hyperuricemia risk. Systemic immune inflammation (SII) was assessed using the SII index and its mediation effects were explored using causal mediation effect model. Results: Data from 10,633 US adults in the NHANES 2003–2018 was analyzed. Except for MEP, individual PAEs metabolite and total PAEs metabolites were associated with increased serum uric acid concentration and hyperuricemia risk. E-R function of PAEs metabolites with serum uric acid concentration and the risk of hyperuricemia showed significantly positive associations with most curves in a nearly linear relationship. WQS regression showed that the mixture of PAEs metabolites was related to elevated serum uric acid and hyperuricemia risk, and MBzP was identified as the most contributing PAEs metabolite. The causal mediation effect model found that SII significantly mediated the relationships of PAEs metabolites with serum uric acid and hyperuricemia risk. Conclusion: Individual and mixture of urinary PAEs metabolites were associated with increased serum uric acid concentration and the risk of hyperuricemia. MBzP exhibited the highest contribution to the overall effects. SII alteration may be an important biological mechanism underlining the impact of PAEs metabolites on serum uric acid concentration and hyperuricemia risk.